Temperature-dependent breakdown and pre-breakdown conduction of polyethylene terephthalate. (8th September 2022) - Zhou, Jierui; Sotzing, Michael; Li, Zongze; Wu, Chao; Zhou, Peinan; Wang, Yifei; Cao, Yang
Abstract: In this paper, electrical conduction of polyethylene terephthalate (PET) films at ultrahigh fields up to breakdown was experimentally investigated using a specially designed circuitry with a dynamic gain-controlled capacitive current cancellation. The breakdown strength of PET is found stable in the temperature range from 25 °C to 100 °C, while the charge-to-breakdown exhibits a dramatic increase over the same temperature range. Furthermore, a turning point is observed around the glass transition temperature ( T g ) of PET for the onset field of the nonlinear conduction. The impact of this secondary transition process in PET on the pre-breakdown conduction is revealed by the Arrhenius analysis, with distinctively different activation energies of 0.70 and 0.22 eV determined for above and below the glass transition temperature, respectively, indicating clearly an increased temperature-dependence of conduction above T g . Explicit space-charge-limited-current features are extracted for the pre-breakdown conduction above T g . With exponential trap distribution model, the characteristic temperature of PET films is extracted from the trap-filling region to be 665 K, and the total trap density is determined to be 1.66 × 10 17 c m − 3 . This study unveils the important role that the physical long-chain topological disorder plays in the electronic and dielectric properties of polymeric dielectrics in association with the secondary transition process. Further study holds the promise for better understanding of underlying physics of breakdown in the design of new polymeric dielectrics.